Lots to spot flashcards Animals - Kelly,Miles (Miles Kelly, 2020)
Lots to Spot Flashcards: Animals! contains 27 double-sided flashcards to teach your preschooler numbers, colours and new words about animals. Improve your toddler's vocabulary, number skills and colour recognition Simple spotting activity on each card Instruction card gives plenty of tips for multiple ways to use the flashcards Lots to Spot Flashcards: Animals! is a captivating set of double-sided flashcards, designed to engage young children as they learn numbers, colours and simple words of both familiar and unusual animals. The bold illustrations encourage learning through playing games and having fun. The durable cards have curved corners and are easy for small hands to hold, making them perfect for use at home and while travelling.
Keywords: Flash cards